Constructing Ecological Experience in ELT Textbook: A Transitivity-based Study of Indonesian Senior High School Narratives - Pranata Lulus Soeparno; Kartika Ning Tyas; Ahmad Misbahudin Taufik; Maria Simatupang; Widhiyanto; Galuh Kirana Dwi Areni (Universitas Islam Negeri Palopo, 2026)
Textbooks play a central role in the EFL classroom are not only as the medium for learning grammar and vocabulary but also as a mediator of social and cultural meanings. This study investigates how experiential meanings are constructed in Indonesian senior high school textbooks through the transitivity system of Systemic Functional Linguistics (SFL). Four narrative texts from English for Change Grade XI (Unit 4: Indonesian Environmental Figures) were segmented into clauses and analyzed in terms of process types, participant roles, and circumstantial elements. A total of 115 clauses were identified. The findings reveal that material processes dominate the data (53 clauses or 46.09%), followed by relational processes (32 clauses or 27.83%), and mental processes (21 clauses or 18.26%). Verbal, behavioral, and existential processes occur marginally. These patterns indicate that environmental experience is primarily represented through observable actions and identity construction, with comparatively limited emphasis on dialogue and reflection. This tendency suggests that ecological issues are pedagogically framed as tangible and action-oriented, potentially facilitating comprehension but constraining opportunities for critical engagement. The study contributes to SFL-based textbook research by demonstratin Textbooks play a central role in EFL classrooms not only as media for learning grammar and vocabulary but also as mediators of social and cultural meanings. This study investigates how experiential meanings are constructed in Indonesian senior high school textbooks through the transitivity system of Systemic Functional Linguistics (SFL), as transitivity patterns reveal how agency, responsibility, and environmental actions are represented in textbook discourse. Four narrative texts from English for Change Grade XI (Unit 4: Indonesian Environmental Figures) were segmented into clauses and analyzed in terms of process types, participant roles, and circumstantial elements. A total of 115 clauses were identified. The findings reveal that material processes dominate the data (53 clauses or 46%), followed by relational processes (32 clauses or 28%), and mental processes (21 clauses or 18%). Verbal, behavioral, and existential processes occur marginally. These patterns indicate that environmental experience is primarily represented through observable actions and identity construction, with comparatively limited emphasis on dialogue and reflection. This tendency suggests that ecological issues are pedagogically framed as tangible and action-oriented, potentially facilitating comprehension but constraining opportunities for critical engagement. The study contributes to SFL-based textbook research by demonstrating how transitivity patterns shape environmental discourse in EFL materials and offers implications for more dialogic and reflective textbook design. g how transitivity patterns shape environmental discourse in EFL materials and offers implications for more dialogic and reflective textbook design.